Solvent Dependency of Sorghum Bran Phytochemicals Acting as Potential Antioxidants and Antibacterial Agents - Tyagi, Varee; Saravanan, Chakkaravarthi; Wang, Yixiang; Bhattacharya, Bhaswati (Food technology and biotechnology, 2021)
Research background. Sorghum bran, although considered as an agricultural waste, is an abundant source of various bioactive compounds. These bioactive compounds require specific extraction with particular solvents and therefore ionic liquid and three different conventional solvents, viz. anhydrous methanol, acidified methanol and water were used in this work. Experimental approach. To evaluate the phytochemicals in the different sorghum bran extracts, total phenol content, flavonoids, condensed tannins and anthocyanins were determined as per standard protocols. Liquid chromatography with tandem mass spectrometry analysis of extracts was also performed for their phenolic profiling. The antioxidant activity of the extracts was estimated via three assays: 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay, 2,2-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical cation decolourization assay and Cu2+ reducing antioxidant capacity (CUPRAC) method. The antibacterial activity against two most opportunistic foodborne pathogens: Escherichia coli and Staphylococcus aureus was measured by agar well diffusion assay and minimum inhibitory concentration (MIC) was determined by serial dilution method. Results and conclusions. Ionic liquid extract of sorghum bran gave the highest yield ((14.9±0.7) %), which indicated that various possible interactions like Van der Waals forces, H-bonding, hydrophobic and cation-π bonding can occur when ionic liquid is used as an extractant compared to other conventional solvents, athough total phenol mass fraction expressed as gallic acid equivalents on dry mass basis was only (7.4±0.7) mg/g. The hydrophobicity of the ionic liquid also helped in efficient extraction of condensed tannins ((63.2±2.1) mg/g expressed on dry mass basis), which resulted in significant antioxidant activity of the ionic liquid extract ((85.2±1.2) µmol/g in DPPH assay, (100.8±0.9) µmol/g in ABTS assay and (63.2±1.9) µmol/g in CUPRAC). An interesting revelation reported in this work is the inability of DPPH assay to evaluate the antioxidant activity in acidic environment. The anhydrous methanolic extract of sorghum bran displayed pH sensitivity, making the extract beneficial for certain applications. Qualitative analysis of extracts revealed greater number of phenolic compounds to be present in methanol and distilled water extracts. Moreover, various derivatives of apigenin and luteolin were also observed in all four extracts. In addition, the acidified methanol extract of the sorghum bran exhibited antimicrobial property at a concentration of 12 mg/mL. A larger inhibition zone was observed against Escherichia coli than Staphylococcus aureus, while the MIC against these two bacteria was 2.2 and 1.1 mg/mL, respectively. Novelty and scientific contribution. This paper presents the first information on the application of ionic liquids as extracting phase for sorghum bran polyphenols and the quantification of such extracts. As evident from the study, each solvent has its own role in the extraction of bioactive compounds. This work also proves that sorghum bran imparts antibacterial activity against foodborne pathogens.